Metabolism and Excretion of [14C]Mobocertinib, a Selective Covalent Inhibitor of Epidermal Growth Factor Receptor (EGFR) Exon 20 Insertion Mutations, in Healthy Male Subjects - Chen, Hao; Shah, Abhi; Kato, Suguru; Griffin, Robert; Zhang, Steven; Pusalkar, Sandeepraj; Cohen, Lawrence; Li, Yuexian; Chowdhury, Swapan K.; Zhu, Sean Xiaochun (Drug metabolism and disposition, 2024)
Mobocertinib (formerly known as TAK-788) is a targeted covalent tyrosine kinase inhibitor of epidermal growth factor receptor with exon 20 insertion mutations. This article describes the metabolism and excretion of mobocertinib in healthy male subjects after a single oral administration of [14C]mobocertinib. Mobocertinib-related materials were highly covalently bound to plasma proteins such as human serum albumin. The mean extraction recovery of total radioactivity was only 3.9% for six individual Hamilton pooled plasma samples. After extraction, mobocertinib was the most abundant component accounting for 7.7% of total extracted circulating radioactivity (TECRA) in the supernatant. Each of identified metabolites accounted for <10% of TECRA. Mobocertinib underwent extensive first-pass metabolism with the fraction of the dose absorbed estimated to be approximately 91.7%. Fecal excretion of mobocertinib metabolites was the major elimination route. Mobocertinib was mainly eliminated via oxidative metabolism with a fraction of approximately 88% metabolized by CYP3A4/5. The other minor elimination pathways included cysteine conjugation, metabolism by other cytochrome P450s, and renal excretion of unchanged mobocertinib. This article describes the metabolism and excretion of a targeted covalent inhibitor mobocertinib in humans after a single oral administration of [14C]mobocertinib. Mobocertinib was highly covalently bound to human plasma proteins. No metabolite accounted for >10% of total extracted circulating radioactivity in human plasma. Mobocertinib was mainly eliminated via CYP3A4/5 mediated oxidative metabolism followed by fecal excretion after approximately 91.7% of the dose was absorbed.